Wacana Iklan Layanan Masyarakat di Koran Mengenai COVID-19: Kajian Makrostruktural - Erwin Salpa Riansi; Yuliarti Yuliarti; Suhailee Sohnui; Achmad Sultoni; Sumarlam Sumarlam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study describes the context of public service advertisements with the COVID-19 theme in the Thairath Thai newspaper October-November 2020 edition. The data were obtained based on the listening method, documentation and note-taking techniques. The speech component (PARLANT) is used to analyze the context. The validity test used is semantic validity. The validity technique used is repeated reading, discussion with colleagues and expert judgment. This research uses a descriptive qualitative approach. The results showed that health advertising discourse always displays product photos that can describe the product in general. The choice of diction in public service advertisements is themed on COVID-19. In conclusion, health advertising discourse always displays photos and illustrations, and the title contains various propositions; the text provides more specific and detailed information. The language used is Thai which is short, concise, exciting and stated in persuasive sentences. Keywords: Discourse Analysis, COVID-19, Public Service Advertising